2020
DOI: 10.1177/0040517520966728
|View full text |Cite
|
Sign up to set email alerts
|

The structural effects on the impact response of ultra-high-molecular-weight polyethylene plain weaves

Abstract: This paper investigates the penetration and energy absorption mechanisms of ultra-high-molecular-weight polyethylene plain weaves with different fabric properties. Impact tests along with finite element (FE) analysis were used to study the impact response of the fabrics. In this research, the impacting projectile did not cause any fiber or yarn failure on the samples. It was found that structural parameters determine the yarn pull-out behavior and the softness of the resultant fabrics. Fabrics formed by loosel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Zhou et al found that penetration is mainly accommodated by yarn pull-out and windowing due to the low yarn-yarn friction and projectile-fabric friction of UHMWPE woven fabrics. 10,11 It follows that producing appreciable friction between the fabric-forming yarns might prove beneficial for the energy absorption capability. The simplest method of increasing inter-yarn friction is to weave tight fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al found that penetration is mainly accommodated by yarn pull-out and windowing due to the low yarn-yarn friction and projectile-fabric friction of UHMWPE woven fabrics. 10,11 It follows that producing appreciable friction between the fabric-forming yarns might prove beneficial for the energy absorption capability. The simplest method of increasing inter-yarn friction is to weave tight fabrics.…”
Section: Introductionmentioning
confidence: 99%